2010
DOI: 10.1038/jhh.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

The Isfahan cohort study: Rationale, methods and main findings

Abstract: A 10-year longitudinal population-based study, entitled the Isfahan Cohort Study (ICS) is being conducted. The ICS commenced in 2001, recruiting individuals aged 35 þ living in urban and rural areas of three counties in central Iran, to determine the individual and combined impact of various risk factors on the incidence of cardiovascular events. After 24379 person-years of follow-up with a median follow-up of 4.8 years, we documented 219 incident cases of ischemic heart disease (IHD) (125 in men and 94 in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 29 publications
(24 reference statements)
2
146
1
Order By: Relevance
“…However, according to our findings, hypertension has a strong association with the risk of IHD as well (RR = 1.90; 95% CI, 1.59-2.26). These findings are similar to those of our previous study (18) and those of other studies such the Honolulu Heart Program that showed that systolic blood pressure and smoking were the most important risk factors of IHD, rather than other risk factors, including high cholesterol level (23). In Iran, the prevalence of hypertension is high, with an increasing trend in recent years (24).…”
Section: Discussionsupporting
confidence: 82%
“…However, according to our findings, hypertension has a strong association with the risk of IHD as well (RR = 1.90; 95% CI, 1.59-2.26). These findings are similar to those of our previous study (18) and those of other studies such the Honolulu Heart Program that showed that systolic blood pressure and smoking were the most important risk factors of IHD, rather than other risk factors, including high cholesterol level (23). In Iran, the prevalence of hypertension is high, with an increasing trend in recent years (24).…”
Section: Discussionsupporting
confidence: 82%
“…Although the in-hospital diagnoses of clinicians were taken into account, the final decisions of the outcome adjudication panel were made independently. A detailed explanation regarding the follow-up is available else- where (14).…”
Section: Follow-up Surveysmentioning
confidence: 99%
“…Measurement of blood pressure and anthropometric parameters were carried out following standard protocols and using calibrated instruments as described previously (14). The waist circumference was taken as the smallest circumference at or below the costal margin.…”
Section: Baseline Surveymentioning
confidence: 99%
“…This study was completed as part of a population-based, longitudinal, ongoing study of healthy Iranian adults aged 35 y and older at the time of recruitment in 2001, known as the Isfahan Cohort Study (ICS) (21). Individuals were selected from three provinces in central Iran, using the multistage random sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…ICS aimed to determine the impact of various risk factors, including individual and environmental risk factors, on the incidence of cardiovascular diseases. Detailed information regarding ICS, including sampling, rationale and results, was presented elsewhere (21,22). In the current study, vitamin D levels were assessed in subjects who were free of MetS in 2001 and if their frozen serum samples were available in 2001, 2007 and 2013.…”
Section: Methodsmentioning
confidence: 99%